EXAMINATION OF SOIL-TRANSMITTED HELMINTHS (STH) IN THE FINGERNAILS AND TOENAILS OF SCAVENGERS AT SUWUNG LANDFILL. - Apriyanthi, Desak Putu Risky Vidika; W, Ayu Saka Laksmita; Widayanti, Ni Putu (BioCONCETTA, 2023)
Scavengers are individuals who gather used items or specific waste for recycling. Scavenging work has resulted in the notion that the scavenger's way of life is an unhealthy lifestyle. The environment and workplace are not conducive and are unclean, so there is a high possibility that scavengers can contract various illnesses, such as coughing, itching, diarrhea, and others. Risk factors for STH worms entering the human body are poor personal hygiene, which can be caused by not being familiar with maintaining proper hand and nail hygiene. Fingernails become a place where worm eggs are attached and can be swallowed when eaten. The purpose of this study was to determine the presence of STH (Soil-Transmitted Helminth) eggs on the fingernails and toenails of scavengers in Suwung landfill. The research design was carried out with an observational study using the cross-sectional method and the results were analyzed with Chi-Square which was carried out by assessing the relationship between the presence of STH eggs and the use of PPE while working. A total of 10 respondents were sampled for their toenails and hands. The results revealed an incidence of STH egg infection in 20% of fingernails and 10% of toenails caused by Ascaris lumbricoides and Trichuris trichiura eggs. A Chi-Square test was performed to examine the correlation between the usage of PPE and the occurrence of STH infection, and a p-value> 0.05 was obtained. Therefore, it can be concluded that there is no strong relationship between both of them.